VD_FINDINFO Arrêt / 2016 / 156 vom 4. Februar 2016 - VD Tribunal cantonal (2016)
CURATELLE, SUBSIDIARITÉ, COMPÉTENCE RATIONE LOCI, RÉSIDENCE HABITUELLE | 389 CC, 390 al. 1 ch. 1 CC, 446 al. 1 CC, 446 al. 2 CC, 446 CC, 450 CC, 85 al. 2 LDIP, 85 LDIP